Communication of personalised disease risk by general practitioners to motivate smoking cessation in England: a cost‐effectiveness and research prioritisation study. (18th January 2022) - Adamson, Alexander; Portas, Laura; Accordini, Simone; Marcon, Alessandro; Jarvis, Deborah; Baio, Gianluca; Minelli, Cosetta
Abstract: Background and Aims: Communication of personalised disease risk can motivate smoking cessation. We assessed whether routine implementation of this intervention by general practitioners (GPs) in England is cost‐effective or whether we need further research to better establish its effectiveness. Design: Cost‐effectiveness analysis (CEA) with value of information (VoI) analysis from the UK National Health Service perspective, using GP communication of personalised disease risk on smoking cessation versus usual care. Setting: GP practices in England. Study population: Healthy smokers aged 35–60 years attending the GP practice. Measurements: Effectiveness of GP communication of personalised disease risk on smoking cessation was estimated through systematic review and meta‐analysis. A Bayesian CEA was then performed using a lifetime Markov model on smokers aged 35–60 years that measured lifetime costs and quality‐adjusted life‐years (QALYs) assigned to the four diseases contributing the most to smoking‐related morbidity, mortality and costs: chronic obstructive pulmonary disease, lung cancer, myocardial infarction and stroke. Costs and QALYs for each disease state were obtained from the literature. VoI analysis identified sources of uncertainty in the CEA and assessed how much would be worth investing in further research to reduce this uncertainty. Findings: The meta‐analysis odds ratio for the effectiveness estimate of GP communication of personalised disease risk was 1.48 (95% credibility interval, 0.91–2.26), an absolute increase in smoking cessation rates of 3.84%. The probability of cost‐effectiveness ranged 89–94% depending on sex and age. VoI analysis indicated that: (i) uncertainty in the effectiveness of the intervention was the driver of the overall uncertainty in the CEA; and (ii) a research investment to reduce this uncertainty is justified if lower than £27.6 million (£7 per smoker). Conclusions: Evidence to date shows that, in England, incorporating disease risk communication into general practitioners' practices to motivate smoking cessation is likely to be cost‐effective compared with usual care.